Quasi-one-dimensional electron gas for ultrahigh sensitivity of ambient light - Liu, Zhenqi; Wang, Lin; Tong, Tong; Xu, Hang; Xue, Yue; Qi, Yaping; Gao, Ju; Ma, Chunlan; Jiang, Yucheng (Applied physics letters, 2024)
Two-dimensional electron gas (2DEG) has drawn significant attention due to its intriguing properties. Recent advances have encouraged the use of one-dimensional electron gas for high-performance functional devices. Here, we develop a universal method of atomic force microscope tip etching to construct a quasi-one-dimensional (Q1D) channel on the STO surface. Ar+ ion beam is used to bombard the SrTiO3 surface for inducing the Q1D electron gas (Q1DEG). Compared with 2DEG, Q1DEG exhibits a significant enhancement in terms of photoconductivity. At room temperature, it exhibits ultrahigh sensitivity to ambient light with increase in photocurrent by over five orders of magnitude. A slow response to the ON/OFF light indicates persistent photoconductivity (PPC), originating from the defect levels. Furthermore, we investigate the wavelength dependence of PPC in Q1DEG. It is found that decreasing wavelength favors photoresponsivity and prolongs the response time. Based on the electron diffusion process in the oxygen-deficient region, a mechanism has been proposed to explain the advantages of Q1DEG over 2DEG in regard to photoelectric response. This work paves a path for the development of high-performance photoelectric devices based on Q1D electronic systems.